Assessment in Jakartan Indonesian Food Reviews: A Case of Nih - Mutiara, Rika (Journal of Modern Languages, 2023)
The present study sheds light on epistemic stance of discourse markers nih on the assessment conducted on YouTube food reviews spoken in colloquial Jakartan Indonesian. Nih indicates speakers’ claim of sharing knowledge. The speakers position themselves as the ones who have knowledge and share it with the watchers who are assumed as the ones with no knowledge of the objects. Mostly, nih is used in the first assessment. In the second assessment, the speakers tend to illustrate the unclear aspect of the first assessment by applying nih. The speakers also apply simile when assessing the dishes to associate the items assessed with more common items. Thus, it will be easier for the audience to comprehend every detail of the assessment. Nih tends to collocate with demonstratives nih, ni, and ini. With the collocations, the speakers guide the hearers to notice the objects or the actions before distributing the knowledge.